2019
DOI: 10.1177/0022219419891412
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of Word Reading as a Predictor of Response to Intervention

Abstract: This study examines the initial word reading performance of fourth-grade struggling readers and the extent to which differing levels of word reading performance at pretest influenced their response to reading interventions. A large group of students with significant reading comprehension difficulties ( N = 481) were classified into three clusters of word reading proficiency based on their pretest performance: (a) very low, (b) low, and (c) near adequate. We examined their performance on several academic, langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 57 publications
3
17
0
Order By: Relevance
“…Wanzek and colleagues (2017) reported that fourth-grade students with reading difficulties’ baseline word recognition scores moderated the association between treatment assignment and posttest reading comprehension scores; treatment group students who began the intervention with higher word recognition scores made greater gains in reading comprehension compared to peers with lower word recognition scores at baseline. Other recent studies have also corroborated these findings (Vaughn et al, 2019, 2020). In their study, the authors (Vaughn et al, 2020) reported that students identified as very low word readers (Standard score < 80) made significantly less growth compared to adequate word readers (Standard score > 90) on three end-of-year standardized reading comprehension measures.…”
Section: Multicomponent Reading Interventionssupporting
confidence: 76%
See 2 more Smart Citations
“…Wanzek and colleagues (2017) reported that fourth-grade students with reading difficulties’ baseline word recognition scores moderated the association between treatment assignment and posttest reading comprehension scores; treatment group students who began the intervention with higher word recognition scores made greater gains in reading comprehension compared to peers with lower word recognition scores at baseline. Other recent studies have also corroborated these findings (Vaughn et al, 2019, 2020). In their study, the authors (Vaughn et al, 2020) reported that students identified as very low word readers (Standard score < 80) made significantly less growth compared to adequate word readers (Standard score > 90) on three end-of-year standardized reading comprehension measures.…”
Section: Multicomponent Reading Interventionssupporting
confidence: 76%
“…Other recent studies have also corroborated these findings (Vaughn et al, 2019, 2020). In their study, the authors (Vaughn et al, 2020) reported that students identified as very low word readers (Standard score < 80) made significantly less growth compared to adequate word readers (Standard score > 90) on three end-of-year standardized reading comprehension measures.…”
Section: Multicomponent Reading Interventionssupporting
confidence: 76%
See 1 more Smart Citation
“…However, recent explorations into initial skill status and intervention response have shown incongruous results. For example, some studies have found students with lower initial skills benefit most from academic interventions (Clarke et al, 2019), whereas others have shown differential response benefiting students with higher pretest achievement (Vaughn et al, 2019). Conversely, findings from other research point to no moderation effects by initial skill levels (Fuchs et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The second category tied response to intervention to well-established linguistic correlates of reading, such as performance in tasks measuring phonological awareness (e.g., Torgesen et al, 1999); vocabulary skills (e.g., Lovett et al, 2017); and rapid naming (e.g., Scheltinga et al, 2010). Finally, some studies examined the predictive power of basic early reading skills (reflecting severity of reading difficulties at baseline), including preintervention word reading skills (e.g., Vaughn et al, 2020). Generally speaking, meta-analyses and systematic reviews of predictors of individual-level responsiveness have likewise focused on these three categories of measures (e.g., Al Otaiba & Fuchs, 2002; Stuebing et al, 2015).…”
mentioning
confidence: 99%